Struktur Modal dan GCG Terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Mediasi di JII - Sri Lestari Kurniawati (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to examine the effect of capital structure and GCG on firm value through profitability as a mediating variable. The population of this research are companies that registered in Jakarta Islamic Index (JII) for the period 2017-2021 with sample selection based on purposive sampling with a total sample of 7 companies. The analysis technique used multiple regression analysis and path analysis. The results of the study are 1) Capital structure has a significant negative effect on firm value, 2) Independent commissioners have no significant effect on firm value, 3) Managerial ownership has no significant effect on firm value, 4) Profitability is able to mediate the effect of capital structure on the firm value, 5) Profitability is able to mediate the effect of independent commissioners on firm value, and 6) Profitability is not able to mediate the effect of managerial ownership on firm value.